The mythic forest, the green man and the spirit of nature : the re-emergence of the spirit of nature from ancient times into modern society - Varner, Gary R. (Algora, 2006)
Mankind has given a recognizable face to the awesome and impalpable forces of nature in the image of the Green Man and the nature spirits that this book explores. The ways in which different societies and different craftsmen have depicted these spirits display the wide creative range of the human imagination, but the persistence of the theme suggests that in all their many facets these spirits represent a deep, primordial sense that humans have shared since civilization began. For the very origin and message of these images have remained the same, even if somewhat altered over time. Traditional customs from around the world, from the rites that celebrate spring and egg on the forces of fertility to folk health remedies and the use of talismans to ward off illness and other evils, show some surprising similarities and hint at the shared origins of human culture. Even though the original significance of many customs has been lost or diluted, they still hold an appeal and many towns even today are re-introducing seasonal fairs to recreate the link between man and nature. Varner presents examples, ancient and new, from Europe and Asia, East Coast and West, and identifies in particular the different guises of the Green Man who has figured in architecture since before the advent of Christianity and still makes his appearance today, peering out from behind his leaves on California banks and New York brownstone houses.